Seetan : Sistem Pengendalian Sosial Masyarakat Desa Pakraman Susut Kelod, Bangli - Hadiputra Evaganna, Made Andika; Sukardja, Putu; Darmana, Ketut (Humanis, 2017)
Social control is needed to overcome the deviant behavior of an individual or group in society. Susut Kelod village has uniqueness to overcome the problem with seetan as a tool of absenteeism in social activities , it perceived that it could create a social order. The implications of a tool of absence its covering a various aspects of the community life. It cause sanctions of shame , fear and also faith in the ancestors , even the establishment of awig - awig is an implied goal that achieved through out the tool itself.